2020
DOI: 10.1590/1980-265x-tce-2020-0235
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Production in Online Journals About the New Coronavirus (Covid-19): Bibliometric Research

Abstract: Objective: to describe the bibliometric indicators of scientific production available in online journals that address Covid-19. Method: bibliometric study using Bradford's Law, network maps and textual statistics conducted with publications available in databases, from January to March 2020. Results: the sample consisted of 110 scientific articles. The main authors of the studies were linked to 83 institutions in 30 countries, giving priority to medical training. China was the country that published the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
0
15
0
8
Order By: Relevance
“…Adopting the short-term analysis technique, Da Silva et al (2020) have examined publication volumes of COVID-19 papers and identified top journals, countries and authors. Similarly, Costa et al (2020) performed keyword analysis and identified the most productive countries, institutions, authors and journals, Lou et al (2020) observed publication types, journals and publication countries, and Gianola et al (2020) identified that during the first five months of the pandemic most of the COVID-19 scientific literature comprised of short reports, opinions and perspectives. Chahrour et al (2020) focused on the international distribution of COVID-19 publications compared with the number of COVID-19 cases in the respective countries, again adopting a short-term analysis approach.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Adopting the short-term analysis technique, Da Silva et al (2020) have examined publication volumes of COVID-19 papers and identified top journals, countries and authors. Similarly, Costa et al (2020) performed keyword analysis and identified the most productive countries, institutions, authors and journals, Lou et al (2020) observed publication types, journals and publication countries, and Gianola et al (2020) identified that during the first five months of the pandemic most of the COVID-19 scientific literature comprised of short reports, opinions and perspectives. Chahrour et al (2020) focused on the international distribution of COVID-19 publications compared with the number of COVID-19 cases in the respective countries, again adopting a short-term analysis approach.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In the field of COVID-19, there have been some research publications focusing on the analysis of the literature from the perspective of bibliometrics. Some of them discussed the global scientific research on COVID-19, and most of these publications analyzed the scientific productions related to COVID-19 (Costa et al, 2020;Dehghanbanadaki et al, 2020;Farooq et al, 2021;Mohadab et al, 2020;Oliveira et al, 2021). Meanwhile, in these publications, some authors summarized the hotspots and explored the future trends of the research (Gautam et al, 2020;Lou et al, 2020;Mao et al, 2020;Yang et al, 2020;Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These considerations portray the potential of SR research for health and, in particular, for nursing, as they favor professionals to better conduct care in a therapeutic plan closer to the logic of the other for whom the care is intended (20) . Such research on COVID-19's SR in nursing is still restricted at the national level (21) , which requires development, as the results may support, within the scope of SUS, nurses' actions in health promotion.…”
Section: Social Practices About Covid-19 and Implications For Nursingmentioning
confidence: 99%